(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Aim : The purpose of this study is to evaluate and compare the effects on food & Nutrition continuous training, interval training, and a combination of both on various physical fitness components—such as endurance, strength, agility, coordination and flexibility—in fencing players.